Effects of an 8-week high intensity interval training (HIIT) and ashwagandha supplementation on aerobic capacity, muscle oxygenation and haematological parameters in healthy men - Jówko, Ewa; Klusiewicz, Andrzej; Rębiś, Kinga; Długołęcka, Barbara; Charmas, Małgorzata; Cieśliński, Igor (Biology of Sport, 2025)
Ashwagandha extract is an herbal dietary supplement with suggested health properties and the potential to improve physical performance. However, there are still few well-controlled studies confirming improvements in aerobic capacity as a result of supplementation, as well as the mechanisms responsible for this effect. The purpose of this randomized, double-blind, placebo-controlled study was to evaluate the effects of ashwagandha supplementation (600 mg/day) on aerobic capacity, muscle oxygenation and resting blood haematological parameters in healthy male non-athletes ’participants undergoing 8 weeks of HIIT. The training was performed on a rowing ergometer (3 sessions per week, 5–7 sets of 1.5 minutes in each session, at a load of 85–95% of maximum aerobic power, and with rest intervals between sets of 1.5 minutes at a power output of 70 W). Aerobic capacity was determined during a maximal graded exercise test on rowing ergometer, performed before and after the 8 week intervention. During this test, muscle oxygenation was monitored using a near-infrared spectroscopy monitor. The two-factor ANOVA (2×2; time×group) revealed no main effect of group and interaction of time and group in the aerobic capacity or haematological parameters ( P > 0.05). In turn, as a result of training, both placebo ( n = 16) and ashwagandha ( n = 17) groups showed large significant improvements in aerobic capacity parameters, i.e. test time, maximal aerobic power and anaerobic threshold (main effect of time, P = 0.00001, post-hoc differences within group; pre-post, P < 0.001; with η 2 amounted 0.60–0.78), with less pronounced changes in maximal oxygen uptake (in absolute terms, main effect of time, P = 0.019; η 2 = 0.16). Furthermore, significant main effect of time and interaction of time and group in some parameters of muscle oxygen utilisation ( P < 0.05; η 2 : 0.15–0.19) were found, and post-hoc analyses showed significant intragroup (pre-post) differences (improvements) in the placebo group ( P < 0.05), but not in the ashwagandha group ( P > 0.05). In conclusion, in healthy men participating in the 8-week HIIT, ashwagandha supplementation (at dose 600 mg daily) does not appear to affect hematological status or offer additional benefitsin aerobiccapacity over those observed under training. Moreover, the inconclusive effect of ashwagandha on training-induced changes in muscle oxygenation needs to be verified in further studies.